Expression and characterization of tissue inhibitor of metalloproteinase 4 from complex canine mammary carcinomas. Issue 5 (2nd September 2016) - Kaur, Navneet; Sunil Kumar, B. V.; Mahajan, Kanika; Singh, Satparkash
ABSTRACT: All four members of the tissue inhibitors of metalloproteinase (TIMP) family have been reported to be over-expressed in breast cancer cells in vitro . Dysregulation of TIMP-4 expression predicts poor prognosis in cancers. The present study evaluated the association of the expression levels of TIMP-4 with mammary tumor development in dogs, measured by real-time quantitative reverse transcriptase polymerase chain reaction (qRT-PCR). Mammary tissue samples were collected from healthy canine mammary gland and from tumor subjects. TIMP-4 expression was found to be upregulated (5.856 times) in complex canine mammary carcinomas. Also, TIMP-4 mature peptide was expressed heterologously in E. coli . The recombinant protein was purified by Ni- NTA affinity chromatography and further confirmed by western blotting. The rTIMP-4 was found to be functionally active and could inhibit matrix metalloproteinase 11(MMP-11) activity. Immunization of mice with rTIMP-4 resulted in increased antigen specific serum antibody titer, and this serum could be suitably used to detect and quantify the protein in sera of dogs with mammary tumors. TIMP-4 could act as a marker of canine mammary tumors. To the best of our knowledge, this is the first report of heterologous expression of TIMP-4 from complex canine mammary carcinomas.